Degradation modelling on the influence of moisture content upon burst capacity of composite repaired pipeline - Chia, Shin Chian (2019)
Pipelines are most favored mode of transportation of gas/liquid in large quantities. Along the service life of steel pipeline system, it exerted in different condition of surrounding which cause deterioration of steel pipeline. There is a rapid growth in the application of Fibre-Reinforced Polymer (FRP) composites wrap where the method has been proven effective for repairing steel pipelines. When composite repair system exposed to aggressive environment, there are various factors which may affect the strength of composite include moisture, temperature, acidity, fire and ultraviolet. This study aims to determine the durability of chopped strand mat glass fibre/epoxy composite under the effect of moisture absorption using finite element analysis (FEA) simulation. The composite was immersed into water for 28 days at room temperature. The moisture contents of composite were 1.078%, 2.758%, 3.693%, 4.100%, and 4.121% on immersion time of 1, 7, 14, 21, and 28 days, respectively. Five finite element models were developed to study the moisture effect toward burst pressure. The FE result shows a slightly drop for burst pressure on 28-days which was 31.663MPa (0.994% drop) with moisture content of 4.121%. The low tensile strength of composite lead to less contribution toward stress sustainability. The moisture effect of composite was not obviously shown by using chopped strand mat glass fibre-epoxy. Although the result shows not much effect of moisture toward the burst pressure, but there was a trend shows the decreasing of burst pressure when moisture content increases. The increase of moisture content decreases the tensile strength of composite and resulted in decreasing of burst pressure. A prediction of long-term service life of composite repaired steel pipe was performed to forecast its remaining service life to demonstrate how the results in this study can be used by the pipeline operators. The burst pressure was predicted to reduce by 53.097% compared to control model which drop from 31.981MPa to 15MPa after 178 days.